Telomere shortening in mucosa surrounding the tumor: Biosensor of field cancerization and prognostic marker of mucosal failure in head and neck squamous cell carcinoma. Issue 5 (May 2015) - Boscolo-Rizzo, Paolo; Rampazzo, Enrica; Perissinotto, Egle; Piano, Maria Assunta; Giunco, Silvia; Baboci, Lorena; Spinato, Giacomo; Spinato, Roberto; Tirelli, Giancarlo; Da Mosto, Maria Cristina; Del Mistro, Annarosa; De Rossi, Anita
<x xml:space="preserve">Abstract</x> Highlights Evaluation of telomere length and levels of TERT in cancer tissues and tumor surrounding mucosa (SM). No correlation was found between age and telomere length in SM. Patients with short telomeres in SM had a significantly higher risk of mucosal failure. Patients with high TERT levels in cancer tissues had a significantly higher risk of regional failure. Telomere erosion is a biosensor of field cancerization and precedes the reactivation of TERT in SM.